Technological diffusion as a recombinant process - Petros Gkotsis; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2016)
In this work we analyse patterns of technological development using patent applications at the United States Patent and Trademark Office (USPTO) over the 1973-2012 period. Our study focuses on the combinations of technological fields within patent documents and their evolution in time, which can be modelled as a diffusion process. By focusing on the combinatorial dimension of the process we obtain insights that complement those from counting patents. Our results show that the density of the technological knowledge network increased and that the majority of technological fields became more interconnected over time. We find that most technologies follow a similar diffusion path that can be modelled as a Logistic or Gompertz function, which can then be used to estimate the time to maturity defined as the year at which the diffusion process for a specific technology slows down. This allows us to identify a set of promising technologies which are expected to reach maturity in the next decade. Our contribution represents a first step in assessing the importance of diffusion and cross-fertilization in the development of new technologies, which could support the design of targeted and effective Research & Innovation and Industrial policies.
Keywords: O33; O31; C10; 330; technological diffusion; patents; knowledge